2009
DOI: 10.1007/s11060-009-0057-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of steroids in the management of brain metastases: a systematic review and evidence-based clinical practice guideline

Abstract: QuestionDo steroids improve neurologic symptoms in patients with metastatic brain tumors compared to no treatment? If steroids are given, what dose should be used? Comparisons include: (1) steroid therapy versus none. (2) comparison of different doses of steroid therapy.Target populationThese recommendations apply to adults diagnosed with brain metastases.RecommendationsSteroid therapy versus no steroid therapyAsymptomatic brain metastases patients without mass effectInsufficient evidence exists to make a trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
188
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(203 citation statements)
references
References 15 publications
3
188
1
2
Order By: Relevance
“…In a study reporting the results of two consecutive randomized trials involving 96 patients with brain metastases, Vecht et al 3 Retrospective studies and reviews report that the most common starting dose of dexamethasone ranges between 8 mg and 16 mg daily 5,6,8,12 . In a recent review of the role of steroids in the management of brain metastases, Ryken and colleagues concluded that symptomatic patients should be treated with a starting dose of 4-8 mg daily; if the patient exhibits severe symptoms associated with increased intracranial pressure, a dose of 16 mg daily or higher could be considered 9 . Two recent comprehensive reviews recommend an initial intravenous loading dose of 10-20 mg dexamethasone when a patient presents with acute neurologic symptoms caused by a brain tumour or spinal cord lesion; the loading dose should be followed by maintenance dosing with oral or intravenous dexamethasone in divided doses totalling to 4-24 mg daily 13,14 .…”
Section: Question 2: Dosingmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study reporting the results of two consecutive randomized trials involving 96 patients with brain metastases, Vecht et al 3 Retrospective studies and reviews report that the most common starting dose of dexamethasone ranges between 8 mg and 16 mg daily 5,6,8,12 . In a recent review of the role of steroids in the management of brain metastases, Ryken and colleagues concluded that symptomatic patients should be treated with a starting dose of 4-8 mg daily; if the patient exhibits severe symptoms associated with increased intracranial pressure, a dose of 16 mg daily or higher could be considered 9 . Two recent comprehensive reviews recommend an initial intravenous loading dose of 10-20 mg dexamethasone when a patient presents with acute neurologic symptoms caused by a brain tumour or spinal cord lesion; the loading dose should be followed by maintenance dosing with oral or intravenous dexamethasone in divided doses totalling to 4-24 mg daily 13,14 .…”
Section: Question 2: Dosingmentioning
confidence: 99%
“…In general, the tapering schedules most commonly reported involve a gradual decrease in the dose or dosing interval over a period of 2-4 weeks to prevent rebound symptoms, with longer periods for symptomatic patients 3,7,8,9,15 . Some publications favour tapering until a physiologic dose equivalent to 20 mg of cortisol daily is achieved, which might be 0.25 mg dexamethasone daily 18,19 .…”
Section: Question 3: Dexamethasone Taperingmentioning
confidence: 99%
“…The studies demonstrated that about 5% patients with gliomas can encounter apoplectic hemorrhage, especially those with glioblastoma (Barkovich et al, 1998;Fiveash et al, 2003;Pina et al, 2014;Ryken et al, 2014;Wang et al, 2014). Glioma hemorrhage is mainly caused by the following factors: a. tumor vascular occlusion and distal vascular necrosis caused by vascular endothelial proliferation, hemangiectasis and vascular distension due to tumor growth as well as invasion of tumor on blood vessels; b. degeneration and necrosis of adjacent tissue structures resulted from tumor infiltration and oppression as well as extended tumor vessels; c. local blood stasis and increased press caused by tumors oppressing adjacent regurgitant vessels; d. changes of tumor haemodynamics due to head trauma and radiotherapy (Fraum et al, 2011;Jo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We have read with interest the review by Ryken et al [1] about the role of imaging in the management of progressive glioblastoma. In general, we agree with this review but we cannot support the opinion that the routine use of Positron-Emission-Tomography (PET) to identify progression of glioblastoma is not recommendable.…”
Section: To the Editormentioning
confidence: 99%